Band offset engineering at C2N/MSe2 (M = Mo, W) interfaces. Issue 19 (20th April 2022) - Slassi, Amine
Abstract : Stacking layered two-dimensional materials in a type-II band alignment block has provided a high-performance method in photocatalytic water-splitting technology. Abstract : Stacking layered two-dimensional materials in a type-II band alignment block has provided a high-performance method in photocatalytic water-splitting technology. The key parameters in such heterostructure configurations are the valence and conduction band offsets at the interface, which determine the device performance. Here, based on density functional theory calculations, the bandgap and band offsets at C2 N/MSe2 (M = Mo, W) interfaces have been engineered. The main findings demonstrate that the C2 N monolayer interacts with both MoSe2 and WSe2 monolayers through weak van der Waals interactions. These heterostructures possess a narrower indirect bandgap and a typical type-II heterostructure feature, being suitable for promoting the separation of photogenerated electron–hole pairs. The calculated Gibbs free energy of hydrogen adsorption demonstrates a reduction in the overpotential, towards the hydrogen evolution reaction, upon forming heterostructures. To further tune the bandgap values and band offsets of heterostructures, the external perturbations are included through a vertical strain and finite electric field. It is found that both the vertical strain and electric field strongly modulate the bandgap values and the magnitude of the band offsets, while the typical type-II band alignment remains preserved. It is noticeable that the band offset magnitudes of the C2 N/MoSe2 and C2 N/WSe2 heterostructures are more sensitive to an external electric field than to a vertical interlayer strain.